Cancer Theranostics: Facile Preparation of Doxorubicin‐Loaded Upconversion@Polydopamine Nanoplatforms for Simultaneous In Vivo Multimodality Imaging and Chemophotothermal Synergistic Therapy (Adv. Healthcare Mater. 4/2015). Issue 4 (March 2015) - Liu, Fuyao; He, Xiuxia; Lei, Zhen; Liu, Liang; Zhang, Junping; You, Hongpeng; Zhang, Huimao; Wang, Zhenxin
Abstract : On page 559, H. M. Zhang, Z. X. Wang, and colleagues directly coat polydopamine (PDA) on hydrophobic upconversion nanoparticle (UCNP) to form UCNP@PDA core–shell nanosphere via a microemulsion approach, further modified with polyethylene glycol (PEG). After loading with DOX, the UCNP@PDA‐PEG‐DOX can completely eradicate mouse‐bearing colorectal cancer without regrowth guided by multimodal imaging, demonstrating highly effective combined photothermal and chemotherapy of the nanocomposites.